2006
DOI: 10.1111/j.1442-9071.2006.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of ocular hysteresis in normal subjects: relevance in clinical context

Abstract: The ocular hysteresis reading was almost constant throughout the day, whereas the IOP readings showed highest values in the morning with a reducing trend being lowest in the afternoon. The CCT values were almost stable throughout the day. IOP appears to vary independently of a variation in hysteresis or CCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 24 publications
8
54
1
5
Order By: Relevance
“…Kida et al (26) , and Laiquzzaman et al (27) found that CH remained almost constant throughout the day, whereas CCT and intraocular pressure showed statistically significant variations (higher values during the nocturnal period) in young adults. The small number of patients in both studies might restrict their findings to these specific populations.…”
Section: Discussionmentioning
confidence: 99%
“…Kida et al (26) , and Laiquzzaman et al (27) found that CH remained almost constant throughout the day, whereas CCT and intraocular pressure showed statistically significant variations (higher values during the nocturnal period) in young adults. The small number of patients in both studies might restrict their findings to these specific populations.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, an increase in CCT values was seen at night but corneal viscoelasticity did not change. 15 This is explained because of the change in hydration state, which can be said for dry-eye syndrome too. Karadayı et al 17 showed that the CCT in dry eyes increases rapidly after application of artificial tears.…”
Section: Discussionmentioning
confidence: 99%
“…According to Laiquzzaman et al 15 CH of normal subjects have the same values in both eyes, so right and left eyes were taken in one group. Diurnal variation of CH was evaluated and it was seen that CH values were steady within 24 h. 15,16 The mean CH value was calculated by three consecutive measurements taken in 5 min. CH was 10.56±0.25 mm Hg in the dry-eye group and 10.34±0.26 mm Hg in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…38 Among these parameters, CH is the one that has been most evaluated in previous studies and is considered an indicator of the viscoelastic properties of the cornea. 31 CH is weakly correlated with CCT, is almost constant throughout the day, 39 and seems unassociated with refractive error or axial length. 40,41 ORA measurements show good within-session repeatability in normal volunteers.…”
Section: Perkins Handheld Tonometer (Medtronic Solan Jacksonville Fmentioning
confidence: 99%